Identification of Compounds With Antiviral Activity Against SARS-CoV-2 in the MMV Pathogen Box Using a Phenotypic High-Throughput Screening Assay - Coimbra, Laís D.; Borin, Alexandre; Fontoura, Marina; Gravina, Humberto D.; Nagai, Alice; Shimizu, Jacqueline Farinha; Bispo-dos-Santos, Karina; Granja, Fabiana; Oliveira, Paulo S. L.; Franchini, Kleber G.; Samby, Kirandeep; Bruder, Marjorie; et al. (Frontiers in Virology, 2022)
Until December 2021, the COVID-19 pandemic has caused more than 5.5 million deaths. Vaccines are being deployed worldwide to mitigate severe disease and death, but continued transmission and the emergence of SARS-CoV-2 variants indicate that specific treatments against COVID-19 are still necessary. We screened 400 compounds from the Medicines for Malaria Venture (MMV) Pathogen Box seeking for molecules with antiviral activity against SARS-CoV-2 by using a high-throughput screening (HTS) infection assay in Vero CCL81 cells. On resupply of 15 selected hit compounds, we confirmed that 7 of them presented a dose-dependent cytoprotective activity against SARS-CoV-2-induced cytopathic effect (CPE) in the micromolar range. They were validated in low-throughput infection assays using four different cell lines, including the human lung Calu-3 cell line. MMV000063, MMV024937, MMV688279, and MMV688991 reduced viral load in cell culture at 20 µM, assessed by RT-qPCR and viral plaque assay, while MMV688279 and MMV688991 (also known as nitazoxanide) were the most promising, reducing SARS-CoV-2 load by at least 100-fold in almost all cell types tested. We tested a series of 40 compounds derived from MMV688279 that led to the identification of MMV1578396, which has a better selectivity index than the previous compound and was more active against SARS-CoV-2 in Calu-3 cells. Our results indicate that active anti-SARS-CoV-2 molecules exist within the repertoire of antiviral, antiparasitic and antimicrobial compounds available to date. Although the mode of action by which MMV688279 and MMV688991 reduce SARS-CoV-2 replication is yet unknown, the fact that they were active in different cell types holds promise not only for the discovery of new therapeutic targets, but also for the development of novel antiviral medicines against COVID-19.